Preservation of Blueschist-facies Minerals along a Shear Zone by Coupled Metasomatism and Fast-flowing CO2-bearing Fluids. (14th August 2014) - Kleine, Barbara I.; Skelton, Alasdair D. L.; Huet, Benjamin; Pitcairn, Iain K.
Abstract: Two types of blue halo (types I and II) composed of blueschist-facies minerals are centered around a brittle, normal shear zone in greenschist-facies rocks on the island of Syros, Aegean Sea, Greece. The shear zone is steeply dipping and cuts a near-horizontal layer of greenschist-facies rocks (albite + epidote + actinolite + chlorite + quartz). Type I and II blue haloes are 0·3 m and c . 1 m wide respectively, and are seen on both sides of the shear zone. The inner type I haloes are composed of nearly pure glaucophane schist and were formed by metasomatic addition of Na2 O and SiO2, and to a lesser extent of K2 O and large ion lithophile elements (LILE), coupled with loss of CaO, Al2 O3 and MnO. The outer type II haloes consist of a carbonated blueschist-facies assemblage (glaucophane + calcite + phengite + epidote + garnet + quartz). These experienced only slight metasomatic changes (i.e. addition of K2 O and LILE), which cannot alone explain halo formation. We present petrological, geochemical and thermodynamic evidence that this assemblage was preserved at greenschist-facies conditions because X CO2 was elevated by flow of a CO2 -bearing fluid along the shear zone, which was approximately contemporaneous with greenschist-facies hydration in the surrounding rocks. We further note that the flux of CO2 -bearing fluid along the shear zone was rapid with respect to the fluid flux in the surrounding rocks. Mass-balance calculations reveal that the fluid flux within the shear zone was at least 100–2000 times greater than the fluid flux within the surrounding rocks. Mineral textures show greenschist-facies minerals replacing blueschist minerals in the type II haloes, supporting our interpretation that the blueschist-facies minerals were preserved during greenschist-facies retrogression. A simplified P–T vs X CO2 pseudosection confirms that preservation of carbonated blueschist can occur at greenschist-facies conditions in the presence of a CO2 -bearing fluid.